A Hyperstitional Machine Appropriating Human Culture in an Evolutionary Fashion - Koutsomichalis, Marinos (My University, 2021)
This paper presents an account of an ecosystemic evolutionary pipeline for the generation of original multimedia content without employing fitness functions or other evaluation schemata. It examines an ongoing art/research endeavour that concerns an experimental creative machine to be ‘plugged-in’ to human culture through the WWW and in order to produce own multimedia content autonomously and unattendedly. The machine employs natural language graphs, as well as intelligent Comprehenders that analyse the retrieved media to further the evolutionary cycle with new queries. It also features a series of algorithmic Composers that mashup and manipulate the retrieved media in various fashions. The overall system is being designed to empirically probe the hypothesis of genuine nonhuman creativity that is built computationaly upon the re-synthesis and the re- appropriation of human culture (through its WWW footprint). The project and the underlying method are announced herein, and a series of technical idiosyncrasies are examined in some detail. Theoretical considerations to the overall approach are further drawn with reference to critical post-humanism.